NQR investigation of crystal structure peculiarities of layered Pbₓ₋₁Cdₓl₂ semiconductors - Gnatenko, Yu.P.; Beinik, I.A.; Barabash, A.I.; Vertegel, I.G.; Chesnokov, E.D.; Ovcharenko, A.I.; Ivanova, L.S. (Functional Materials, 2008)
The ¹²⁷l NQR spectra of semiconductor mixed crystals Pbₓ₋₁Cdₓl₂ at 77 K have been investigated. It is shown that at low values of Cdl₂ concentration, the intra-layer symmetry of the basic crystal becomes distorted considerably. This occurs due to formation of the intra-layer mechanical strains which are defined by the size difference between the main and impurity atoms (Pb and Cd, respectively). At x>0.10, intra-layer heterophasic two-dimensional Cdl₂ islets have been shown to be formed. The results are discussed that evidence the formation of amorphous glassy phase of the mixed Pbₓ₋₁Cdₓl₂ crystal at x>0.10. Досліджено спектри ¹²⁷l ЯКР нових напівпровідникових змішаних кристалів Pbₓ₋₁Cdₓl₂ при 77 К. Показано, що при низьких значеннях концентрації Cdl₂ відбувається значне викривлення внутрішньошарової симетрії базового кристала Pb₂ . Це є наслідком формування внутрішньошарових механічних напруг, котрі визначаються різницею розмірів основних та домішкових атомів (відповідно РЬ та Cd). Показано, що при х>0,1 утворюються внутрішньошарові гетерофазні (острівкові) структури Cdl₂. Обговорюються питання відносно утворення склоподібної фази змішаного кристала Pbₓ₋₁Cdₓl₂ при х>0,1. Исследованы спектры ¹²⁷l ЯКР новых полупроводниковых смешанных кристаллов Pbₓ₋₁Cdₓl₂ при 77 К. Показано, что при низких значениях концентрации Cdl₂ происходит существенное искажение внутрислоевой симметрии базового кристалла Pb₂. Это происходит благодаря формированию внутрислоевых механических напряжений, которые определяются различием размеров основных и примесных атомов (соответственно РЬ и Cd). Показано, что при х>0,10 образуются внутрислоевые гетерофазные (островковые) структуры Cdl₂. Обсуждаются результаты, указывающие на образование стеклоподобной аморфной фазы смешанного кристалла Pbₓ₋₁Cdₓl₂ при х>0,10.